2020
DOI: 10.1039/c9an01664c
|View full text |Cite
|
Sign up to set email alerts
|

A dual-enzyme, micro-band array biosensor based on the electrodeposition of carbon nanotubes embedded in chitosan and nanostructured Au-foams on microfabricated gold band electrodes

Abstract: We report the development of a dual-enzyme electrochemical biosensor based on microfabricated gold band array electrodes which were first modified by gold foam (Au-foam) in order to dramatically increase the active surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The shelf life of these sensors was reported to be 45 days. Chronoamperometry was used to detect glucose in the linear range of 0.05 mM to 1.1 mM with an LOD of 0.025 mM [ 157 ].…”
Section: Recent Developments In Various Biological Fluid-based Glucos...mentioning
confidence: 99%
“…The shelf life of these sensors was reported to be 45 days. Chronoamperometry was used to detect glucose in the linear range of 0.05 mM to 1.1 mM with an LOD of 0.025 mM [ 157 ].…”
Section: Recent Developments In Various Biological Fluid-based Glucos...mentioning
confidence: 99%
“…However, as mentioned earlier, part of the challenge with these systems arises from the molecular structure of the enzyme itself. Many attempts have been made to try to create a successful matrix for the transfer of electrons between the FAD and the electrode by integration of conductive polymers and emerging nanomaterials such as carbon-based nanomaterials (carbon nanotubes [10][11][12][13][14], graphene [15][16][17], carbon/graphene quantum dots [18][19][20], etc. ), metal nanoparticles [21][22][23][24][25] (gold, silver, copper, etc.…”
Section: Enzymatic and Non-enzymatic Electrochemical Biosensorsmentioning
confidence: 99%
“…The electrodeposition of chitosan films is one of the common methods now used in biosensor development [ 77 , 78 , 79 ]. For example, very recently, Juska et al [ 14 ] have reported a biosensor towards glucose based on a two-step electrodeposition process, Figure 6 c. Firstly, these workers achieved the deposition of gold foam on to a microfabricated gold electrode array in acidic environment at high negative applied voltage. Then, an organic functional layer was electrodeposited on to the gold foam surface which consisted of chitosan and multiwalled carbon nanotubes.…”
Section: Enzymatic and Non-enzymatic Electrochemical Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-walled carbon nanotubes (MWCNTs) is one of the most widely used carbon materials but their applications are normally limited due to their hydrophobic nature. MWCNTs can be functionalized with biomolecules and metal oxide nanoparticles, surfactants and polymers to reinforce the surface properties for challenging the limits [19]. Therefore, a novel electrochemical biosensor based on Fe 3 O 4 À CSÀ CD/MWCNTs/GOx was fabricated for eletrodetection of glucose in this work.…”
Section: Introductionmentioning
confidence: 99%